PPARβ/δ directs the therapeutic potential of mesenchymal stem cells in arthritis. Issue 12 (8th March 2016) - Luz-Crawford, P; Ipseiz, N; Espinosa-Carrasco, G; Caicedo, A; Tejedor, G; Toupet, K; Loriau, J; Scholtysek, C; Stoll, C; Khoury, M; Noël, D; Jorgensen, C; et al.
Abstract : Objectives: To define how peroxisome proliferator-activated receptor (PPAR) β/δ expression level in mesenchymal stem cells (MSCs) could predict and direct both their immunosuppressive and therapeutic properties. PPARβ/δ interacts with factors such as nuclear factor-kappa B (NF-κB) and regulates the expression of molecules including vascular cell adhesion molecule (VCAM)-1 and intercellular adhesion molecule (ICAM)-1. Since these molecules are critical for MSC function, we investigated the role of PPARβ/δ on MSC immunosuppressive properties. Methods: We either treated human MSCs (hMSCs) with the irreversible PPARβ/δ antagonist (GSK3787) or derived MSCs from mice deficient for PPARβ/δ (PPARβ/δ −/− MSCs). We used the collagen-induced arthritis (CIA) as model of immune-mediated disorder and the MSC-immune cell coculture assays. Results: Modulation of PPARβ/δ expression in hMSCs either using GSK3787 or hMSCs from different origin reveals that MSC immunosuppressive potential is inversely correlated with Ppard expression. This was consistent with the higher capacity of PPARβ/δ −/− MSCs to inhibit both the proliferation of T lymphocytes, in vitro, and arthritic development and progression in CIA compared with PPARβ/δ +/+ MSCs. When primed with proinflammatory cytokines to exhibit an immunoregulatory phenotype, PPARβ/δ −/− MSCs expressed a higher level of mediators of MSC immunosuppression including VCAM-1, ICAM-1 and nitric oxide (NO) than PPARβ/δ +/+ MSCs. The enhanced NO2 production by PPARβ/δ −/− MSCs was due to the increased retention of NF-κB p65 subunit on the κB elements of the inducible nitric oxide synthase promoter resulting from PPARβ/δ silencing. Conclusions: Our study is the first to show that the inhibition or knockdown of PPARβ/δ in MSCs primes their immunoregulatory functions. Thus, the regulation of PPARβ/δ expression provides a new strategy to generate therapeutic MSCs with a stable regulatory phenotype.